Interventions Using Social Media for Cancer Prevention and Management: A Systematic Review. Issue 6 (November 2018) - Han, Claire Jungyoun; Lee, Young Ji; Demiris, George
Abstract : Background: Regarding cancer awareness, social media effectively promotes health and supports self-management. Given the diverse study designs, methodologies, and approaches of social media interventions in oncology, it is difficult to determine the effects of social media on cancer prevention and management. Objective: We aim to systematically review intervention studies using social media for cancer care. Methods: A systematic search, using 7 electronic databases (PubMed, Web of Science, CINAHL, Cochrane Library, Scopus, EMBASE, and PsycINFO), was conducted to identify surveys and interventions using contemporary social media tools with a focus on cancer. Results: Of the 18 selected studies, 7 were randomized controlled trials. Most studies were conducted for all types of cancer, and some were conducted for breast cancer in the United States, with mostly white female participants. Facebook was the most frequently used platform. Most studies targeted healthy participants providing cancer prevention education. With social media platforms as part of a larger intervention, or the main component of interventions, interventions were overall feasible and showed a significant improvement in cancer prevention and management. Conclusions: Social media tools have the potential to be effective in delivering interventions for cancer prevention and management. However, there was a dearth of studies with rigorous study methodologies to test social media effects on various cancer-related clinical outcomes. Implications for Practice: Social media use in cancer care will facilitate improved communication and support among patients, caregivers, and clinicians and, ultimately, improved patient care. Clinicians need to carefully harness social media to enhance patient care and clinical outcomes. Abstract : Supplemental digital content is available in the text.